Influences of factors of human resources for innovation in services companies - Mazini, Sergio Ricardo; Ulian, Elisângela [UNESP] (My University, 2014)
The chapter aims to understand how human factors influence and contribute to have an organizational climate conducive to creativity and innovation in service companies. The chapter also proposes an analytical framework to assess the influence of human resources, and understanding how they contribute to that has a climate conducive to innovation. The proposed methodology is the multiple case study and qualitative research in Brazilian companies. The analyses and discussions identify that conducting innovative decentralized actions may harm the process, and efficient management practices, such as the use of collaborative work, skills assessment, and identification of technology trends, assist in the innovation process.